Karakterisasi Pelet Pupuk Organik Berbahan Eco Enzyme: Characterization Of Organic Fertilizer Pellets Eco enzyme - Winaningsih, Ima; Suramta, Suramta; Mala, Yanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Eco enzyme has nutrients for liquid organic fertilizer. However, the eco enzyme's N, P, K elements are still below the quality standard. Liquid organic fertilizer is disadvantaged in handling, packaging, use, and transportation compared to pellet form. Nutrient levels can be increased through fish bones and rice bran addition. This research aims to determine the characteristics of the best pellets based on Ministry of Agriculture quality standards No. 261/2019, such as length, diameter, density, water content and N, P, K levels. The eco enzyme, water, fish bones, and rice bran’s formula were: C1 (1: 0: 1: 1), C2 ( ¾: ¼: 1: 1 ), and C3 ( ½: ½: 1: 1). Pellets were made by mixing the ingredients with 5% tapioca solution. The tools used to measure pellet length, diameter, and pH were caliper and pH meter. The water content using the gravimetric method. The N, P, and K levels were tested at BALISTA Lembang, Bandung. All formulations’ pellet length and diameter averaged ±12 mm and 4 mm. Water content of C1, C2, and C3 pellets were 8.63%, 8.97%, and 9.18%, respectively. pH of C1, C2, and C3 pellets were 5.7, 5.8, and 5.9, respectively. Particle density for C1, C2, and C3 were 1.37 g/cm3, 1.44 g/cm3, and 1.46 g/cm3, respectively, while the bulk densities were 0.58 g/cm3, 0.63 g/cm3, and 0.64 g/cm3, respectively. The N, P, K levels in C1, C2, and C3 were 5.2%, 4.79% and 4.3%, respectively. C3 is the best formulation. All pellets meet quality standards.